HIBAH UNTUK ANAK DIBAWAH UMUR MENURUT PERSPEKTIF HUKUM ISLAM - CUT JANIATI (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2021)
Human in order to live their live, they will always have needs,both in the form of physical and spiritual needs. One of the physical needs can be obtained by someone either by entering into a sale and purchase agreement, exchange, leasing, inheritance or by way of grants, namely giving to someone when the person giving to someone when the person giving is still alive and cannot be represented by a third party on behalf of the giver except for a court decision. Implementation of grants to minors who are under guardianship or to people who are able do not have direct material rights to everything they receive must go through a guardianship or guardian for people who are able to be authorized by a person appointed by the sultan in court. While the implementation of grants for minor who are under the authority of their parents, grants for movable property are sufficient for direct delivery. Auntentic deed, must be made with a clear and clear pledge which in acceptance is carried out by being represented by the guardian of the child in the case the guardianship rights of the blood family and the gift guardian have legal or legal force.